Towards an understanding of online visual aesthetics: An instantiation of the composition perspective. (May 2021) - Longstreet, Phil; Valacich, Joseph; Wells, John
Abstract: This article articulates the importance of developing a Theory of Online Visual Aesthetics in the IS tradition, and demonstrates that to date the field is still lacking a theoretical model for explaining online visual aesthetics. To address this gap in the literature the authors propose the Online Visual Aesthetics Theoretical Model, drawn from over 100 years of literature in complementary disciplines. The Online Visual Aesthetics Theory Model proposes that the perception of the composition of an online medium is directly influenced by the eight web design categories: Graphics, Text, Simplicity, Animation, Layout, Unity, Emphasis, and Balance. The variance of each of these web design categories may then be explained by the more traditional seven primary design dimensions: Lines, Shapes, Colors, Textures, Forms, Values, and Spaces. The final instantiated Online Visual Aesthetics Theoretical Model is then presented and a program of study is articulated for the evaluation and validation of the proposed theoretical model. Highlights: Online visual appeal often treated as subjective. Research provides theoretical underpinning to understanding online visual appeal. Develops theoretical model of visual appeal utilizing a multidisciplinary approach. Treats online visual appeal as a composition of different elements.